2008
DOI: 10.1128/jvi.01615-07
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Heterosubtypic Immunity to Influenza Virus by Intranasal Immunization

Abstract: Recovery from live influenza virus infection is known to induce heterosubtypic immunity. In contrast, immunity induced by inactivated vaccines is predominantly subtype specific. In this study, we investigated the heterosubtypic protective immunity induced by inactivated influenza virus. Intranasal immunization of mice with inactivated influenza virus A/PR8 (H1N1) provided complete protection against the homologous virus and a drift virus within the same subtype, A/WSN (H1N1), but not against the heterosubtypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
167
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 136 publications
(167 citation statements)
references
References 37 publications
(49 reference statements)
0
167
0
Order By: Relevance
“…Influenza VLP vaccines can increase the speed of vaccine production in part because they are manufactured using cell culture instead of the cumbersome egg-based manufacturing methods in use today for inactivated virus-based vaccines (39). In this study, we propose that influenza VLP vaccination can be further expedited by administration using a microneedle patch applied to the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza VLP vaccines can increase the speed of vaccine production in part because they are manufactured using cell culture instead of the cumbersome egg-based manufacturing methods in use today for inactivated virus-based vaccines (39). In this study, we propose that influenza VLP vaccination can be further expedited by administration using a microneedle patch applied to the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these observations, the immunological basis of heterosubtypic immunity against influenza A virus infection and the contribution of the Tc-cell response remain important areas of research. Importantly, in order to investigate the underlying mechanism for heterosubtypic immunity, many researchers have used low doses of live viruses to prime animals prior to heterosubtypic challenge (8,16,28,38,41,55). It has been reported that in vivo depletion of CD4 ϩ or CD8 ϩ T cells (8,14,28,30,41) or of both T-cell subsets (14) had only a minor effect on heterosubtypic protection.…”
mentioning
confidence: 99%
“…A/PR/8/34 virus grown in egg allantoic fluids was purified using sucrose-gradient ultracentrifugation and inactivated using formalin (0.1%) as described. 30 Korean red ginseng extract (ginseng extract), a concentrated form of the commercial ginseng product for human use, was kindly provided by Korea Ginseng Corp. (Daejeon, Korea). In brief, fresh roots of P. ginseng that had grown for 6 years were washed, steamed at 100°C for 2-3 h, and dried.…”
Section: Cells Virus and Reagentsmentioning
confidence: 99%
“…30 In brief, lungs were collected at Day 4 postinfection with A/California/4/2009 virus or a mixture of A/California/4/2009 virus and ginseng extract. Serially diluted lung extracts were added to six-well plates containing confluent MDCK cell monolayers and incubated at 37°C for 1 h. Overlay medium containing DEAE dextran, nonessential amino acids, glutamine, and trypsin was added and incubated for 2 or 3 days.…”
Section: Lung Viral Titers and Cytokine Assaysmentioning
confidence: 99%
See 1 more Smart Citation